Type II Secretion Is Necessary for Optimal Association of the Legionella-Containing Vacuole with Macrophage Rab1B but Enhances Intracellular Replication Mainly by Rab1B-Independent Mechanisms - White, Richard C. (Infect Immun, 2016)
Previously, we documented that type II secretion (T2S) promotes intracellular infection of macrophages by Legionella pneumophila. In the present study, we identified infection events that are modulated by T2S by comparing the behaviors of wild-type and T2S mutant bacteria in murine bone marrow-derived macrophages and human U937 cells. Although the two strains behaved similarly for entry into the host cells and evasion of lysosomal fusion, the mutant was impaired in the ability to initiate replication between 4 and 8 h postentry and to grow to large numbers in the Legionella-containing vacuole (LCV), as evident at 12 h. At 4 h postinoculation, mutant LCVs had a significantly reduced association with Rab1B, a host GTPase that facilitates the tethering of endoplasmic reticulum (ER)-derived vesicles to LCVs. The mutant did not lose expression or translocation of six type IV secretion effectors (e.g., SidM) that are well known for mediating Rab1B association with the LCV, indicating that T2S promotes the interaction between the LCV and Rab1B via a novel mechanism. Interestingly, the mutant's growth defect was exacerbated in macrophages that had been depleted of Rab1B by short hairpin RNA (shRNA) treatment, indicating that T2S also potentiates events beyond Rab1B association. In support of this, a sidM lspF double mutant had an intracellular growth defect that was more dramatic than that of the lspF mutant (and a sidM mutant) and showed a growth difference of as much as a 400-fold compared to the wild type. Together, these data reveal a new role for T2S in intracellular infection that involves both Rab1B-dependent and Rab1B-independent processes.